USING DIFFERENT TYPES OF ASSESSMENTS IN LANGUAGE TEACHING IN ESP GROUPS - Makhammadjonova, Nafisa Abdurashid qizi (Educational Research in Universal Sciences, 2023)
This article is dedicated using different types of assessments in teaching English ​​to non-philological ESP groups. The competences shouldn’t be or cannot be developed in separation or by segregated way; vice versa language is also social event which should be taught in relation with real world situations and conditions. The work challenges to teach proper tips which can be practical in Uzbek cultural context and interlink into its objectives communicative and sociolinguistic competences.